(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Making packaging more sustainable has garnered increasing interest over the past 20 years from all relevant parties (government, businesses, and consumers). One of the most environmentally friendly materials on the market is paper. 60 participants took part in focus group sessions that were organised in two rounds as part of a qualitative study that examined customers’ expectations and perceptions about sustainable paper-based packaging materials. Participants in the first stage discussed their perspectives on the packages that are currently on the market as well as their expectations for a sustainable packaging material. They assessed five paper-based prototype packages for two product categories (biscuits and meat) in the study’s second phase. The main concerns for present products were excessive plastic use and over packaging. The two key factors influencing consumers’ buying intentions were price and quality. Although the prototypes’ sustainability impressed the participants, they weren’t entirely satisfied with the design and weren’t willing to pay more for a more eco-friendly box. The "3Rs"—Reduce, Reuse, and Recycle—should be the primary factors to consider when creating a sustainable package, according to the major message that came out of the conversations.